Enhancing The Formability of SS304 in ISF via Pre-Heating Treatment Strategies - Shah, Muhammad Aqib Raza; Saragih, Agung Shamsuddin (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
The increasing demand for lightweight yet high-strength components in the automotive and aerospace industries has accelerated interest in Incremental Sheet Forming (ISF) as a flexible, dieless, and cost-effective manufacturing process, particularly for low-volume and customized production. Unlike conventional forming processes that rely on expensive dies, ISF offers greater geometric flexibility and rapid prototyping capabilities. However, its broader industrial adoption remains limited due to persistent challenges such as poor surface finish, springback, and restricted formability, especially when forming hard-to-deform materials like Stainless Steel Grade 304 (SS304). This study investigates the influence of customized heat treatment on the formability and deformation quality of SS304 sheets formed via ISF. Sheets were subjected to preheating at controlled temperatures ranging from room temperature to 700°C, followed by dieless forming using a CNC machining center equipped with a hemispherical tungsten carbide tool. Key process parameters, including a step size of 0.3 mm, a feed rate of 180 mm/min, and a tool speed of 500 mm/min, were maintained throughout forming. Comprehensive mechanical and microstructural analyses, including tensile testing, surface roughness evaluation, and optical metallography, were performed. Results revealed significant improvements in formability: ductility increased from 24.28% to 65%, and surface roughness (Ra) decreased from 9.7993 µm to 5.4809 µm after annealing at 700°C and tempering at 500°C. Microstructural analysis confirmed grain refinement and carbide dissolution, contributing to improved plastic flow and reduced surface defects. Integrating controlled heat treatment with ISF significantly enhances forming capabilities, surface quality, and geometric precision of SS304, making it a viable solution for manufacturing complex, high-performance components. These findings provide valuable insights for developing more efficient, defect-minimized, and adaptable forming strategies suitable for advanced manufacturing industries.